Perancangan system Kendall rotary-crane scale laboratorian mengunakan model state space - Purtojo; Mahdi, Nur Amiral; Suryawan , Donny; Adi, Agung Nugroho (Prosiding SNTTM, 2023)
A crane transports heavy goods using a tall structure to move from one point to another within a certain distance. The rotary crane can be modeled as a simple rotary pendulum on an experimental scale. As a controlled object, the model is used to simulate the control performances that are appropriate for crane use. The angular position of the pendulum arm and link are the main objects to be controlled. A smaller pendulum link swing and fast pendulum arm reach the final position without or with a small overshoot, which is desired. The space space model of the rotary pendulum is derived since it represents the multi-input-multi-output system. The state feedback control was then developed to design the control system. The integral time absolute error performance index was set as the desired performance within the operation range. The controller gain K was obtained based on the system's performance index and characteristic equation. The simulation was then conducted in a computer model using the Xcos model provided by Scilab software to iterate the best value of controller gain K. The simulation result was implemented as a controlled object in the rotary pendulum. The rotary pendulum is driven by a DC motor with a rotary encoder attached to it to track its position. The angular swing pendulum is tracked using a rotary encoder as well. Hardware in the loop configuration was built to experiment.